Mechanisms Underlying Graft Union Formation and Rootstock Scion Interaction in Horticultural Plants - Rasool, Aatifa; Mansoor, Sheikh; Bhat, K. M.; Hassan, G. I.; Baba, Tawseef Rehman; Alyemeni, Mohammed Nasser; Alsahli, Abdulaziz Abdullah; El-Serehy, Hamed A.; Paray, Bilal Ahmad; Ahmad, Parvaiz (Frontiers in Plant Science, 2020)
Grafting is a common practice for vegetative propagation and to improve the traits in horticultural and agricultural plants. A general prerequisite for grafting to be successful in the first place and secondly for the grafts to survive for a longer period is taxonomic proximity. For the success of a grafting operation, rootstock and scion should essentially be closely related. Interaction between the rootstock and scion involves complex physiological-biochemical and molecular mechanisms. Successful graft union formation involves a series of steps viz., lining up of vascular cambiums, followed by generation of a wound healing response, callus bridge formation, ultimately the vascular cambium formation is completed and subsequent formation of the secondary xylem and phloem takes place. Graft incompatibility occurs because of unfavorable physiological responses across the graft union, transmission of virus or phyto-plasma and anatomical deformities of vascular tissue at the graft junction. In order to avoid the incompatibility problems, it is important to predict the incompatibility at an early stage. Phytohormones, especially auxins regulate key events in graft union formation between the rootstock and scion, while others function to facilitate the signaling pathways. Transport of macro as well as micro molecules across long distances results in phenotypic variation shown by grafted plants, therefore grafting can be used to determine the pattern and rate of recurrence of this transport. A better understanding of rootstock scion interactions, endogenous growth substances, soil or climatic factors needs to be studied, which would facilitate efficient selection and use of rootstocks in the future. For the grafted trees compatibility between the rootstock/scion is the most essential factor for their better performance and longevity. Protein, hormones, mRNA and small RNA transport across the junction is currently emerging as an important mechanism which controls the stock/scion communication and simultaneously may play a crucial role in understanding the physiology of grafting more precisely.